1984
DOI: 10.1164/arrd.1984.129.5.719
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Bronchitis

Abstract: We have assessed bronchial mucous gland size in a group of 26 patients with severe chronic air-flow obstruction and hypoxemia from the NIH Nocturnal Oxygen Therapy Trial. These patients had their sputum volume assessed at least 4 times when free from exacerbations. Mucous gland size was assessed by the gland/wall ratio (Reid Index), by absolute gland area, and by the volume proportion of glands. The volume of sputum produced was significantly related to the volume proportion of mucous glands (Rho = 0.53, p les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…If this occurs for three months in the year for at least 2 successive years in the absence of known lung diseases associated with mucus production e.g. Measurements of bronchial gland size do not correlate with airflow obstruction [12]. The term "chronic bronchitis" for this clinical syndrome has produced much confusion and is best avoided, as it has been used interchangeably by some to equate COPD, whereas in fact longitudinal studies have shown that chronic cough and sputum production does not predict decline in FEV1 [9,10].…”
Section: Central Airwaysmentioning
confidence: 99%
“…If this occurs for three months in the year for at least 2 successive years in the absence of known lung diseases associated with mucus production e.g. Measurements of bronchial gland size do not correlate with airflow obstruction [12]. The term "chronic bronchitis" for this clinical syndrome has produced much confusion and is best avoided, as it has been used interchangeably by some to equate COPD, whereas in fact longitudinal studies have shown that chronic cough and sputum production does not predict decline in FEV1 [9,10].…”
Section: Central Airwaysmentioning
confidence: 99%